Aspectos biologicos de sorghum halepense (L.) Pers. II- Capacidad vegetativa - La O, F.=700 1 Labrada, R.; Garcia, R.C.; Hernandez, F.; Plana, L.
(Es, En)
Ilus., 9 ref.
Keywords: SORGHUM HALEPENSE; EXPERIMENTACION EN CAMPO; MALEZAS; BIOLOGIA; CUBA